Understanding consumers’ addiction to online mobile games and in apps purchase intention: Players stickiness as the mediation - Pantas H Silaban; Andri Dayarana K. Silalahi; Edgar Octoyuda (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2021)
Research on consumer behavior, particularly on online mobile games, is an emerging topic that must be more deeply explored. As a relatively new topic, the approach and discussion of consumer behavior based on the online mobile games environment challenge researchers to describe it in a theoretical study. This research investigates the user's addiction to online mobile games (OMG) in apps purchase intention through a stickiness mediation variable. The samples were determined by using purposive random sampling, which consisted of gamers or people who were playing online mobile games and ever purchase a games feature. Therefore, a total of 439 responses were collected through an online survey. This research employs SmartPLS 2.0 to test both measurement and structural models. The results showed that the addiction to online mobile games influenced app purchase intention, and stickiness also mediated the relationship between addiction to online mobile games and app purchase intention. The contribution of this research emphasizing that the addiction to online mobile games had become a behavior that created stickiness and intention is also discussed in this research.